Our Experiences in Initiating Implementation of Electives at a Bilawal Medical College, Liaquat University of Medical and Health Sciences, Jamshoro, Sindh Pakistan - Piryani, Rano Mal; Soomro, Abdul Ghani; Ahmadani, Shahzad; Asif, Razia; Shaikh, Asiya Parveen (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
Electives supplement to the core curriculum of undergraduate health professions education, thereby enriches personal and professional development of undergraduates in diverse areas. Electives provide an opportunity for transformative learning. This paper describes the implementation of electives at newly established Bilwal Medical College for Boys, a constituent college of Liaquat University of Medical Health Sciences, Jamshoro, Sindh, Pakistan. Firstly, concrete policy for electives was developed by health professions educationist. Then Committee for the implementation of electives was constituted. Subsequently, feasible and achievable implementation plan was formulated focusing on the activities to be done before, during and after the placement of students for electives in different departments and process of implementation. The first batch of students studying in fourth year of MBBS attended the electives. With keen involvement of all stakeholders such as, students, faculty, administration, parents and collaborating departments and their faculty, the program was successfully implemented. Thorough supervision and monitoring during placement contributed toward the success of program.